1997
DOI: 10.1128/iai.65.3.943-950.1997
|View full text |Cite
|
Sign up to set email alerts
|

Decoration of lipopolysaccharide with phosphorylcholine: a phase-variable characteristic of Haemophilus influenzae

Abstract: Choline, although not a nutritional requirement for Haemophilus influenzae, is taken up from the growth medium and incorporated into its lipopolysaccharide (LPS). Incorporated choline is in the form of phosphorylcholine (ChoP) based on the reactivity with the monoclonal antibody with specificity for this structure, TEPC-15. Incorporation of [ 3 H]choline from the growth medium and expression of the TEPC-15 epitope undergo high-frequency phase variation, characteristic of other LPS structures in this species. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
194
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(200 citation statements)
references
References 49 publications
3
194
0
3
Order By: Relevance
“…A third, well-described interaction mechanism involves phosphorylcholine, a cell-surface molecule that mediates bacterial adherence to host cell receptors. Phosphorylcholine is expressed by both S. pneumoniae [28] and H. influenzae [29], and seems to contribute to the competitive effect between these two species through its immunogenicity [30]. Pre-exposure to one of the two species induces the production of antibodies against phosphorylcholine, thereby promoting clearance of the other co-colonizing species [30,31].…”
Section: Bacterial Mechanisms Of Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…A third, well-described interaction mechanism involves phosphorylcholine, a cell-surface molecule that mediates bacterial adherence to host cell receptors. Phosphorylcholine is expressed by both S. pneumoniae [28] and H. influenzae [29], and seems to contribute to the competitive effect between these two species through its immunogenicity [30]. Pre-exposure to one of the two species induces the production of antibodies against phosphorylcholine, thereby promoting clearance of the other co-colonizing species [30,31].…”
Section: Bacterial Mechanisms Of Interactionmentioning
confidence: 99%
“…Pre-exposure to one of the two species induces the production of antibodies against phosphorylcholine, thereby promoting clearance of the other co-colonizing species [30,31]. Since in vitro studies have shown that phosphorylcholine is necessary for the survival of pneumococci but not H. influenzae, the latter may switch off phosphorylcholine expression to give it an advantage over S. pneumoniae [29,31]. The host immune system is also involved in interspecies competition, as has been elegantly shown in vivo by Lysenko et al [32].…”
Section: Bacterial Mechanisms Of Interactionmentioning
confidence: 99%
“…Subspectra corresponding to the individual glycosyl residues were identified on the basis of J-connectivity pathways delineated in the 1 H chemical shift correlation maps, the chemical shift values, and the vicinal coupling constants. 13 C resonances were assigned by heteronuclear 1 H± 13 C chemical shift correlation in the 1 H detected mode (HMQC) and the data are presented in Tables 3 and 6. The chemical shift data are consistent with each d-sugar residue being present in the pyranosyl ring form.…”
Section: Isolation and Characterization Of Lpsmentioning
confidence: 99%
“…In accord, C-6 of Glc I in the LPS-OH and Fr. 1 oligosaccharides gave 13 (Table 4). In addition, the subspectrum of a b-linked GalNAc was recognized from the characteristic chemical shift values for H-2 (d 3.95) and C-2 (d 53.5) (Tables 4 and 6).…”
Section: Structure Of Hex3 Glycoformsmentioning
confidence: 99%
“…As a nutritional requirement for S. pneumoniae, choline is taken up from the growth medium, and incorporated as PC into the capsular polysaccharide and cell membrane lipoteichoic acid [10]. Although not nutritionally required by H. influenzae, choline is incorporated into its lipooligosaccharide [11]. These findings suggest that PC is a vaccine candidate that is potentially protective against both S. pneumoniae and H. influenzae infections.…”
Section: Introductionmentioning
confidence: 95%